Effect of Schema-Based Learning on Reducing the Symptoms of Secondary Traumatic Stress in Wives of Post-Traumatic Stress Disorder Veterans - Kh. Abolmaali; A. Kamal (Afarand Scholarly Publishing Institute, 2015)
Aims: Secondary trauma is considered as a similar syndrome to post-traumatic stress disorder that is caused indirectly and through close contact with victims. This study aimed to examine the effects of schemes-based model training in reducing the symptoms of secondary traumatic stress and its dimensions (re-experiencing of the event, avoidance, and arousal) in the spouses of veterans with post-traumatic stress disorder. Instruments & Methods: In this quasi-experimental study with pretest-posttest and control group, 24 spouses of veterans with post-traumatic stress disorder from 2006 to 2013 had been admitted to the Sadr Psychiatric Hospital of Tehran were studied. The subjects were randomly assigned to two experimental (n=12) and control (n=12) groups. Data collected using demographic questionnaire, depression, anxiety and stress scale and Secondary Traumatic Stress Scale. Schema-based approach learning was done in 12 sessions with 2h. Data were analyzed by univariate and multivariate covariance. Findings: In the posttest phase, the mean score of secondary trauma symptoms in experimental group was significantly lower than control group. There was a significant difference between mean scores of two groups regarding disturbing, avoidance and arousal symptoms (p<0.01). Conclusion: Schema-based instruction is an effective method for reducing of the symptoms of secondary trauma and its components (disturbing, avoidance and arousal) in the spouse of veterans with post-traumatic stress disorder.